The anti gender hate speech on social networks as a form of violence against women and a form of hate speech - Igareda González, Noelia (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
The article addresses the problem of anti-gender hate speech issued by political parties that are increasingly proliferating on social networks. They represent a conflict of fundamental rights, between freedom of expression, ideological freedom, freedom of communication, political pluralism, and the right to equality, the right to honor, privacy and one’s own image and human dignity. The applicable legal framework varies from the criminalisation of hate speech in the most serious cases, to the absence of any intervention in a virtual context, or depending of private companies that own these social networks. Finally, these anti-gender hate speeches are analyzed as forms of violence against women that requires the intervention of the State, and legislative activity to guarantee the fundamental rights at stake.
Keywords: anti gender hate speech; social networks; political parties; freedom of expression